A 39-kDa capsular protein is a major cross-protection factor as demonstrated by protection of chickens with a live attenuated Pasteurella multocida strain of P-1059 - Nattawooti Sthitmatee (2018)
The aim of this study was to show that a 39-kDa protein or OmpH of Pasteurella multocida strain P-1059 is essential for cross protection. Strain PBA322, a thinly capsulated strain of P. multocida strain P-1059, was used as a live vaccine in chickens. Strain PBA322 is a thinly capsulated strain in comparison with the parental strain P- 1059. Chickens were vaccinated by single injection and then challengeexposed with strains P-1059 or X-73 at two weeks post vaccination. Moreover, immune responses were also evaluated for both humoral and cellular immune response by ELISA and lymphocyte proliferation assay, respectively. The results showed that the live vaccine induced efficient immunity to protect chickens from challenge-exposure to the parent strain, but that the heterologous protection was poor. We concluded that the 39-kDa protein is essential for cross protection. © 2013 The Japanese Society of Veterinary Science.